Effect of sodium on repair weldability of SUS316FR for a fast breeder reactor. Issue 2 (1st February 2016) - Chun, Eun Joon; Baba, Hayato; Nishimoto, Kazutoshi; Saida, Kazuyoshi
Abstract : The effect of sodium on repair weldability of SUS316FR steel under the remaining sodium environment was investigated by transverse-Varestraint and laser cladding tests. Solidification brittle temperature range (BTR) of SUS316FR steel with AF solidification mode was 37 K. However, BTR was expanded from 37 to 67 K, as the amount of surface-adhered sodium increased from 0 to 7.99 mg/cm 2 . From microstructural observation of the weld metal, there would be a possibility that metallic sodium existed at cell boundaries in the weld metal during welding solidification. According to the thermodynamic calculation, the sodium would expand the solid–liquid coexistence temperature range. It could be concluded that the enhanced solidification cracking susceptibility under the sodium environment would be attributed to the enlargement of the solid–liquid coexistence temperature range. Finally, it was confirmed that any solidification cracks and blowholes did not occur in the overlaid weld metal through multipass laser cladding tests. Namely, it could be confirmed that SUS316FR steel possessed superior repair weldability under the sodium environment.